Impact of Recommended Resources in a Mobile Learning Environment on Self-Regulated Learning Abilities among Higher Education Students - Jing, Xiaoyue (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rapid development of mobile technology, mobile learning has increasingly become a significant trend in higher education. Offering flexibility in time and space, online learning introduces new opportunities and challenges for student education. Particularly, the potential of mobile learning to foster students’ self-regulated learning (SRL) abilities remains largely untapped. SRL abilities refer to students’ capacity to proactively set goals, manage resources, monitor progress, and evaluate outcomes during the learning process, which is crucial for learning effectiveness. Although existing research has started to examine the impact of mobile learning on students’ self-regulation abilities, there is still a significant lack of quantitative analysis of students’ learning resource preferences and the development of personalized recommendation methods based on the preferences. This study aims to quantitatively analyze the learning resource preferences of higher education students and propose a novel, preference- based equitable recommendation method for mobile learning to support their SRL. The anticipated results are expected to provide theoretical and methodological support for higher education practices, enhance students’ SRL abilities, and offer new strategies for the effective utilization of mobile learning resources.